1992
DOI: 10.1111/j.1398-9995.1992.tb00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational asthma in the confectionary industry caused by sensitivity to egg

Abstract: We report on a patient with asthma induced by occupational exposure to egg used to spray cakes before baking. A type I hypersensitivity to egg white was demonstrated by means of skin test, immunoassay for specific IgE, and immediate bronchial provocation test response to an egg white extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The risk to a baker of developing baker's asthma is estimated at 0.3% per year. 71 Other implicated foods reported to cause occupational asthma include egg, 72 enzymes used in the cheese industry, 73 shellfish, 74 milk, 75 and carob bean flour. 76 Pathologically, occupational asthma looks similar to allergic asthma.…”
Section: Occupational Asthmamentioning
confidence: 99%
“…The risk to a baker of developing baker's asthma is estimated at 0.3% per year. 71 Other implicated foods reported to cause occupational asthma include egg, 72 enzymes used in the cheese industry, 73 shellfish, 74 milk, 75 and carob bean flour. 76 Pathologically, occupational asthma looks similar to allergic asthma.…”
Section: Occupational Asthmamentioning
confidence: 99%
“…Food handlers are at risk of developing dermatitis due to food sensitization or skin damage directly from their irritant effects, as well as from the wet environment that accompanies food preparation. When the allergen is volatile, respiratory and ocular symptoms (rhinitis, asthma, and conjunctivitis) can coexist [12, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that adult patients with one or more food allergies had increased hospitalizations for asthma [ 4 ], and in a study from Woods et al, it was shown that adults with probable peanut and shrimp allergy often have more frequent asthma episodes and doctor’s diagnosed asthma [ 9 ]. In addition, it has been also shown that inhalation of aerosolized food particles may lead to the development of asthma in adults [ 10 12 ]. The relation between asthma and gastrointestinal symptoms in adults is not extensively studied.…”
Section: Introductionmentioning
confidence: 99%